Diagnóstico do uso de tecnologia da informação como estratégia para implementação das práticas de governança de TI em IES - Brandão, Dhyego Silva Domingos (2021)
Governance in Information Technology (TI) is configured as a resource capable of supporting and enabling the improvement, advice and audit of the quality of TI services. In order for this governance to work, means and techniques are developed to provide and enable services. In this way, this work aims to diagnose the use of information technology as a strategy for the implementation of UNEMAT governance practices of TI. It presents the concepts of TI governance as a theoretical foundation, in addition to the most recent versions of the best practice guides most used worldwide. It is characterized as an exploratory descriptive research with a qualitative approach. As for the technical procedures, it is a case study and documentary research, with a survey of institutional data collected from the managers and TI teams of the UNEMAT Campuses, through an interview and the application of a questionnaire. It is believed that the results of this research will assist in the identification of possible weaknesses in the current TI structure of UNEMAT in relation to TI Governance practices and, consequently, will enable the recommendation of best practice guides, which will collaborate so that the University TI can be aligned with institutional actions, in order to achieve the strategic objectives proposed by senior management.